Morphological study of the digestive tract of the cardinal tetra, Paracheirodon axelrodi (Characiformes: Characidae) - Rincón Camacho, Laura (2023)
The cardinal tetra Paracheirodon axelrodi is a species of the family Characidae of great interest as an ornamental fish. Many aspects of the biology of this species are still unknown. The present work presents a complete description of the different components of the digestive tract of P. axelrodi, analyzing its global anatomical arrangement, the adjacent glands (liver and pancreas) and the previously ignored pyloric caeca, using histological and histochemical techniques with light microscopy and scanning electron microscopy. Three levels of analysis were performed: macroscopic anatomy, histology of the gastrointestinal tract and scanning electron microscopy of mucosal surfaces. The intestinal coefficient (Ci) of P. axelrodi calculated here (0.94) is within the expected range for a carnivorous species. The anatomy of the alimentary and the resulting Ci is consistent with carnivorous diet in line with dietary studies in the wild in this species. The digestive tract, including adjacent glands (liver and pancreas), presented a relatively conserved general pattern within that described for other species of the family Characidae, especially at the histological level.